Nucleobase-containing compounds evoke behavioural, olfactory, and transcriptional responses in model fishes - Angela L. Shamchuk; Brian J. Blunt; Danielle D. Lyons; Mo Qi Wang; Anastasia Gasheva; Carlie R. Lewis; Kirsten Tomlin; E. Starr Hazard; Gary Hardiman; Keith B. Tierney (Canadian Science Publishing, 2018)
The sensory system of animals detects a massive and unknown array of chemical cues that evoke a diversity of physiological and behavioural responses. One group of nitrogen-containing carbon ring chemicals-nucleobases-are thought to be involved in numerous behaviours yet have received little attention. We took a top-down approach to examine responses evoked by nucleobases at behavioural, tissue, and gene expression levels. Fish generally avoided nucleobases, and this behaviour, when observed, was driven by purines but not pyrimidines. At the tissue level, olfactory neuron generator potential responses tended to be concentration specific and robust at concentrations lower than amino acid detection ranges. In terms of gene expression, more than 2000 genes were significantly upregulated following nucleobase exposure, some of which were expected (e.g., genes involved in purine binding) and some of which were not (e.g., tubulin-related genes). Humanized RNA pathway analysis showed that we had exposed the animal to a nucleobase. Our data indicate that responses to nucleobase-containing compounds may be highly structure based and are evident from changes in behaviour to mRNA expression. Many of these responses were surprising, and all provide numerous routes for further research endeavour.